Characterization and full implementation of temporal correlation algorithms for microcirculation velocimetry - Capulong, Jihan O. (2004)
Blood velocity provides useful information on the functions, state, and dynamics of the microcirculation system that is useful in medical diagnosis and microcirculation research. Parameters such as blood flow, perfusion of blood to tissues, and concentration of nutrients in cells can be derived from blood velocity. To obtain a measure of blood velocity, a Blood Velocimeter is used. This research project implements a blood velocimeter as a stand-alone unit using the Jackrabbit BL1810 microcontroller with the Rabbit 2000 microprocessor from the Z-World. It is programmed using Dynamic C, an integrated embedded-system development software based on the C-language designed for programming Z-World microcontrollers and microprocessors. Improvement of the photo-detector module was done by characterization of the photo-transistor used by obtaining its output signal amplitude from various light intensities. Based on the characteristics, the logarithmic amplifier was employed and characterized showing an improved dynamic range and sensitivity of the photo-detector module.
Thesis (B.S. Electronics and Communications Engineering)--University of the Philippines, Diliman.
Keywords: Blood Flow Velocity; Microcirculation; Particle image velocimetry; Blood velocimeter; Temporal correlation algorithms